Prospects for lithium treated patients with severe renal impairment - Harald Aiff; Per-Ola Attman; Mihaela Golic; Bernd Ramsauer; Staffan Schön; Steinn Steingrimsson; Jan Svedlund (International Journal of Bipolar Disorders)
Abstract Objectives To study the prospects for lithium treated patients who develop end stage renal disease (ESRD) and the role of renal replacement therapy (RRT). Methods Retrospective analysis of survival, somatic comorbidity, lithium treatment and eligibility for renal replacement therapy in adult patients with at least one eGFR < 30 ml/min/1.73 m2. Subjects were selected from our laboratory database (s-Lithium and s-creatinine) from 1980 to 2017. Results 620 (14%) of 4396 patients with a lithium history had at least one measurement of eGFR < 30 ml/min/1.73 m2. 302 (49%) patients had a transient decrease in renal function with subsequent improvement, 135 (22%) patients died with acute renal failure, while 153 (25%) developed chronic kidney disease stage 4 (CKD4) and 33 (5%) required RRT. RRT-treated patients represent only a fraction of the total ESRD population. Median survival time from the debut of CKD4 was 13.9 years in patients < 65 years and 4.4 years in older patients. 100 of the 153 patients with CKD4 continued lithium treatment. There was no significant difference in survival after the debut of CKD4 between the patients who stopped lithium treatment and those who continued. Conclusions A measurement of eGFR < 30 ml/min/1.73 m2 reflects a significant loss of renal function. In half of the patients it was due to a transient functional disturbance without long-term consequences. A quarter of patients had acute renal failure and died within days while the remaining quarter progressed to CKD4. Despite irreversible renal damage, patient survival can be counted in several years after debut of renal insufficiency with appropriate care including RRT. As the treating psychiatrist, it is important to consult with nephrology when renal function starts to deteriorate, to optimise somatic treatment.